2009
DOI: 10.1007/s12010-009-8626-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Characterization of an Endoglucanase from a Symbiotic Protist of the Lower Termite, Reticulitermes speratus

Abstract: RsSymEG, an endoglucanase of glycosyl hydrolase family (GHF) 7 encoded by a transcript isolated from the symbiotic protist of the termite Reticulitermes speratus, is expressed in Aspergillus oryzae. Interestingly, purified RsSymEG1 has a relatively higher specific activity (603 micromol min(-1) mg(-1) protein) and V(max) value (769.6 unit/mg protein) than previously reported data for GHF7 endoglucanase of Trichoderma ressei. It also has the same K(m) value (1.97 mg/ml) with Clostridium cellulolyticum enzymes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
2
29
1
Order By: Relevance
“…These results indicated that AfSwo1 exhibited endoglucanase activity toward CMC. However, compared with other endoglucanases (26), the specific activity of endoglucanase in AfSwo1 was very low at 2.6 U/mg. Disruption activity of AfSwo1 toward crystalline cellulose.…”
Section: Downloaded Frommentioning
confidence: 73%
“…These results indicated that AfSwo1 exhibited endoglucanase activity toward CMC. However, compared with other endoglucanases (26), the specific activity of endoglucanase in AfSwo1 was very low at 2.6 U/mg. Disruption activity of AfSwo1 toward crystalline cellulose.…”
Section: Downloaded Frommentioning
confidence: 73%
“…With respect to microbial and termite cellulases, recent literature surveys of native and recombinant enzymes identified optimal pH and temperature ranges, respectively, of 3.6-9.0 and 45-1001C (Viikari et al, 2007;Todaka et al, 2010). Results for recombinant R. flavipes Cell-1 and engineered versions of a homologous endoglucanase from R. speratus expressed in E. coli (Ni et al, 2007) were very similar (pH$7, 40-501C) and were intermediate relative to the microbial activity ranges noted above.…”
Section: Stability Of Bev-expressed Cell-1mentioning
confidence: 86%
“…Alternatively, a homologous endoglucanase from C. formosanus showed highest CMC activity at pH 5 and reduced temperature stability above 371C (Zhang et al, 2009). Similarly, a recombinant symbiotic GHF 7 exoglucanase from R. speratus expressed in Aspergillus oryzae showed optimal CMC activity at pH 6.5 and 451C (Todaka et al, 2010). Thus, BEVS-expressed recombinant Cell-1 shows slightly improved temperature stability characteristics at neutral pH relative to a number of other recombinant termite endoglucanases.…”
Section: Stability Of Bev-expressed Cell-1mentioning
confidence: 95%
See 1 more Smart Citation
“…Enzymes such as glycosyl hydrolases which are highly active in the hydrolysis of crystalline cellulose, have been revealed by metatranscriptomic analyses of symbiotic protozoal communities from four termites species and a wood-eating cockroach (Todaka et al 2009). Enzymatic activities such as amylases and proteases have also been detected in crude extracts of hindgut's protozoa (Kane 1997).…”
mentioning
confidence: 99%